Role of technical assistance in U.S. labor and health sector collaboration to address precarious work. (22nd December 2020) - Bonney, Tessa; Welter, Christina; Jarpe-Ratner, Elizabeth; Velonis, Alisa; Conroy, Lorraine
Summary: Precarious work has recognized adverse impacts on the health of workers; however, there are few policy, systems and environmental (PSE) change public health interventions that target the causes and consequences of precarious work. To build the capacity of health organizations to develop and implement such interventions, researchers engaged representatives from health organizations in a six-session learning process, entitled the healthy work collaborative. Representatives of labor organizations were engaged as technical assistance (TA) providers, which involved sharing content and skill knowledge with health participants. Semi-structured interviews were conducted with providers and participants to examine perceptions of the role of TA; providers' motivations for providing TA; and providers' and participants' perceptions of the impact of TA on learning and preparing for subsequent intervention. Results suggest that the provider–participant engagement evolved from one-way knowledge translation to a robust, two-way knowledge exchange with potential for collaborative intervention development and implementation. These results highlight the ways in which this provider–participant model facilitated engagement between representatives from sectors that had not previously worked together and suggests that such a model may be effective in catalyzing multi-level, multi-sectoral PSE change to address precarious work.